Three local Us in top 100 ranking - Daily Express, (KK) (Daily Express (KK), 2016)
KUALA LUMPUR: Three Malaysian universities made it to the top too list out of the 300 universities, involving 50 countries, of the Times Higher Education (THE) BRIG'S and Emerging Economies University Rankings 2017.